On the attenuation of the axisymmetric longitudinal waves propagating in the bi-layered hollow cylinder made of viscoelastic materials - Kocal, Tarik; Akbarov, Surkay D. (TECHNO-PRESS, 2017)
The paper studies the attenuation of the axisymmetric longitudinal waves propagating in the bi-layered hollow cylinder made of linear viscoelastic materials. Investigations are made by utilizing the exact equations of motion of the theory of viscoelasticity. The dispersion equation is obtained for an arbitrary type of hereditary operator of the materials of the constituents and a solution algorithm is developed for obtaining numerical results on the attenuation of the waves under consideration. Specific numerical results are presented and discussed for the case where the viscoelasticity of the materials is described through fractional -exponential operators by Rabotnov. In particular, how the rheological parameters influence the attenuation of the axisymmetric longitudinal waves propagating in the cylinder under consideration, is established.
Keywords: wave attenuation; wave dispersion; viscoelastic material; characteristic creep time; long-term elastic constants; COMPOUND CYLINDER; ELASTIC-WAVES; COATED PIPES; DISPERSION; PLATES; SCATTERING; DEFECTS; MODEL; Engineering